Macrophage Mediated Immunomodulation During Cryptococcus Pulmonary Infection - Wang, Yan; Pawar, Siddhi; Dutta, Orchi; Wang, Keyi; Rivera, Amariliz; Xue, Chaoyang (Frontiers in Cellular and Infection Microbiology, 2022)
Macrophages are key cellular components of innate immunity, acting as a ﬁrst line of defense against pathogens to modulate homeostatic and inﬂammatory responses. They help clear pathogens and shape the T-cell response through the production of cytokines and chemokines. The facultative intracellular fungal pathogen Cryptococcus neoformans has developed a unique ability to interact with and manipulate host macrophages. These interactions dictate how Cryptococcus infection can remain latent or how dissemination within the host is achieved. In addition, differences in the activities of macrophages have been correlated with differential susceptibilities of hosts to Cryptococcus infection, highlighting the importance of macrophages in determining disease outcomes. There is now abundant information on the interaction between Cryptococcus and macrophages. In this review we discuss recent advances regarding macrophage origin, polarization, activation, and eﬀector functions during Cryptococcus infection. The importance of these strategies in pathogenesis and the potential of immunotherapy for cryptococcosis treatment is also discussed.